2018
DOI: 10.1051/0004-6361/201833013
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved spectroscopy across stellar surfaces

Abstract: Context. Spectroscopy across spatially resolved stellar surfaces reveals spectral line profiles free from rotational broadening, whose gradual changes from disk center toward the stellar limb reflect an atmospheric fine structure that is possible to model by 3D hydrodynamics. Aims. Previous studies of photospheric spectral lines across stellar disks exist for the Sun and HD 209458 (G0 V) and are now extended to the planet-hosting HD 189733A to sample a cooler K-type star and explore the future potential of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
4
7
0
Order By: Relevance
“…Czesla et al 2015;Yan et al 2017), the RM effect (see e.g. Cameron et al 2010;Cegla et al 2016;Dravins, Gustavsson & Ludwig 2018;Bourrier et al 2018), or stellar activity (see e.g. Cauley et al 2018), whereas the later is of main importance especially for this work and demonstrated in Fig.…”
Section: Re-investigating the K I Absorption On Hd189733bmentioning
confidence: 78%
See 1 more Smart Citation
“…Czesla et al 2015;Yan et al 2017), the RM effect (see e.g. Cameron et al 2010;Cegla et al 2016;Dravins, Gustavsson & Ludwig 2018;Bourrier et al 2018), or stellar activity (see e.g. Cauley et al 2018), whereas the later is of main importance especially for this work and demonstrated in Fig.…”
Section: Re-investigating the K I Absorption On Hd189733bmentioning
confidence: 78%
“…where g 2 is the statistical weight of the upper level, A 21 the Einstein A-coefficient, ν 0 the wavenumber of the transition, E 1 the energy of the lower level, Q the partition function, and T the temperature. The values for g 2 and A 21 are taken from Draine (2011), while E 1 is zero because the resonance lines are ground-level transitions. The line profile is modelled by a Voigt profile, consisting of a Doppler core and Lorentzian line wings, where the standard deviation of the Doppler profile σ D is given by ) with the molecular mass of the species m. The Na I and K I resonance lines are well known for possessing a far-wing line profile that is non-Lorentzian (e.g.…”
Section: A P P E N D I X a : S Y N T H E T I C T R A N S M I S S I O N S P E C T R Amentioning
confidence: 99%
“…For the cooler K1 V star HD 189733A (Alopex), such an effect is neither expected nor observed (Paper III; Dravins et al 2018). Further modeling constraints may come from the strongest (partly chromospheric) lines, such as Ca II H and K, or Na I D 1 and D 2 , where limb brightening in their wings relative to the adjacent continuum has been seen (Czesla et al 2015).…”
Section: Spectra From 3d Hydrodynamic Atmospheresmentioning
confidence: 94%
“…Cegla et al (2018) inspected the impact of the granulation on the resultant line profiles and found induced center-to-limb variations in shape and net position. Dravins et al (2017Dravins et al ( , 2018 scrutinised the possibility to study stellar microvariability highlighting small surface segments, hidden behind the planet transits, with high spectral resolution observations.…”
Section: Introductionmentioning
confidence: 99%